2016
DOI: 10.1016/j.jtho.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hypofractionated High-Dose Radiotherapy in Poor-Risk Patients with “Ultracentral” Non–Small Cell Lung Cancer

Abstract: Unfit patients with ultracentral tumors who were treated using this scheme had a high local control and a median survival of 15.9 months. Despite manifestation of rates of a fatal lung bleeding comparable to those seen with conventional radiotherapy for endobronchial tumors, the overall rate of G5 toxicity is of potential concern. Additional work is needed to identify tumor and treatment factors related to hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(193 citation statements)
references
References 25 publications
5
186
2
Order By: Relevance
“…Organs at risk contouring was adopted from RTOG 0813, EORTC LungTech, SUNSET, and RTOG 1106 contouring atlas, and normal tissue constraints were adopted from RTOG 0813 and previous HILUS studies . Meanwhile, maximum point dose and volumetric maximum dose analyses were evaluated for OAR including esophagus, heart, pulmonary artery, pulmonary vein, spinal cord, ipsilateral lung, contralateral lung, lung total, trachea, mainstem bronchi, lobe bronchi, and proximal bronchial tree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organs at risk contouring was adopted from RTOG 0813, EORTC LungTech, SUNSET, and RTOG 1106 contouring atlas, and normal tissue constraints were adopted from RTOG 0813 and previous HILUS studies . Meanwhile, maximum point dose and volumetric maximum dose analyses were evaluated for OAR including esophagus, heart, pulmonary artery, pulmonary vein, spinal cord, ipsilateral lung, contralateral lung, lung total, trachea, mainstem bronchi, lobe bronchi, and proximal bronchial tree.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In the 2010s, a new subgroup within the cohort of patients with central tumors was designated as "high-risk" or "ultra-central" tumors, or those that abut the PBT. 7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Ultra-central tumors have increased grade 4+ toxicity, even with conservative radiotherapy fractionation. 25 Of concern, Haseltine et al reported that in patients with PBT-abutting tumors who received conservative dose-fractionation SBRT plus bevacizumab, two patients experienced grade 5 pulmonary hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…Tekatli et al 84,85 report the outcomes of 80 patients with tumour PTV within 2 cm of the proximal bronchial tree and 47 patients with more ultracentral tumours, defined as the PTV in contact with the trachea or main bronchi. The patients were treated with 60 Gy/ 8# (BED for tissue with an alpha/beta ratio of 10 5 105 Gy).…”
Section: Sabr For Central Lesions In Lung Cancermentioning
confidence: 99%
“…Fatal pulmonary haemorrhage was observed in 15% of patients. 85 The promising reported outcomes and toxicity profile, as well as the prognostic sequelae of not adequately treating ES central lung cancer would suggest that SABR will be offered to these patients with increasing frequency. 86 However, those patients with tumours involving the trachea or main bronchus will be at a much higher risk of treatment toxicity, including death.…”
Section: Sabr For Central Lesions In Lung Cancermentioning
confidence: 99%
“…Some reports have discussed the definition of ultracentral lung cancer. Tekatli et al . defined “ultracentral” lung cancer as centrally located NSCLC with planning target volume (PTV) overlapping the trachea or main bronchi.…”
Section: Introductionmentioning
confidence: 99%